Effects of Acupuncture on Behavioral Stereotypies and Brain Dopamine System in Mice as a Model of Tourette Syndrome - Lin, Lixue; Yu, Lingling; Xiang, Hongchun; Hu, Xuefei; Yuan, Xiaocui; Zhu, He; Li, Hongping; Zhang, Hong; Hou, Tengfei; Cao, Jie; Wu, Shuang; Su, Wen; et al. (Frontiers in Behavioral Neuroscience, 2019)
Tourette syndrome (TS), a developmental neurobehavioral disorder, is characterized by involuntary behavioral stereotypies. Clinical studies have confirmed the positive effect of acupuncture on treating TS, but the underlying mechanisms are not fully understood. In the present study, we used behavioral tests, western blotting, double-immunofluorescence labeling, and fluorescence spectrophotometry to investigate whether acupuncture performed at acupoints “Baihui” (GV20) and “Yintang” (GV29) affected behavioral stereotypies and regulated the dopamine (DA) system in three different brain regions in Balb/c mice injected with 3, 3'-Iminodipropionitrile (IDPN) as a model for TS. We found that acupuncture alleviated behavioral stereotypies, down-regulated the expression of D1R and D2R in the striatum (STR) and substantia nigra pars compacta (SNpc), and decreased the concentration of DA in the STR, SNpc, and prefrontal cortex (PFC) as well. Moreover, acupuncture reduced the expression of tyrosine hydroxylase (TH) in the SNpc. Conclusively, acupuncture ameliorated behavioral stereotypies by regulating the DA system in the STR, SNpc, and PFC. Our findings provide novel evidence for the therapeutic effect of acupuncture on TS.